Identification of atrial fibrillation associated genes and functional non-coding variants - Antoinette F. van Ouwerkerk (Nature Portfolio, 2019)
The majority of disease-associated genetic variants lie in non-coding regions. Here the authors generated and compiled human transcriptomic, epigenomic and chromatin conformation datasets, to identify genes associated with atrial fibrillation and functional non-coding variants.